Pengaruh Pemilihan Umum Tahun 2024 Terhadap Abnormal Return dan Trading Volume Activity - Br Bangun, Dini Febriana; Vina Arnita (Journal of Trends Economics and Accounting Research, 2024)
This research is entitled "The Influence of the 2024 General Election on Abnormal Returns and Trading Volume Activity". This study aims to find out whether there is a difference in the average abnormal return and trading volume activity before and after the 2024 election in IDX30 companies listed on the Indonesia Stock Exchange. The variables of this study are abnormal returns and trading volume activity. The population used in this study is companies listed on the IDX and included in the IDX 30 Index stock group.The method used in sampling is saturated sampling, the sampling method if all members of the population are sampled, namely all companies on the IDX that are included in the IDX 30 Index. The data analysis technique of this study uses the Paired Sample t-Test. This study uses an observation period of five days before the February 14, 2024 election and five days after the February 14, 2024 election. The results of this study show that the average abnormal return (0.993 > 0.05) which means that there is no difference between the average abnormal return before and after the 2024 election and the average trading volume activity (0.049 < 0.05) there is a difference in the average trading volume activity before and after the 2024 election on companies that are members of the IDX 30 index on the IDX.